Cerium-nitrogen synergistically modified composite lithium ion sieve, and preparation method and application thereof
Patent Information
- Application Number
- CN202611127840.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-09-15
AI Technical Summary
[0010]本发明的目的在于克服偏钛酸锂离子筛存在的吸附容量有限、吸附动力学较慢、循环稳定性不足等问题,提供一种铈氮协同改性的偏钛酸复合型锂离子筛及其原位制备方法
[0033] Beneficial effects: The Ce and N synergistic modification of H2TiO3 composite lithium-ion sieve of the present invention modifies the H2TiO3 lithium-ion sieve through Ce and N synergistic doping, simultaneously realizing the formation of CeO2 heterostructure interface and N element doping, synergistically promoting the reconstruction of material electronic structure, oxygen vacancy generation and interface electronic coupling, and improving Li-O3 lithium-ion sieve performance. + This significantly improves the lithium adsorption capacity, selectivity, and cycle stability of lithium-ion sieves by enhancing transport efficiency and ion exchange capacity. 4+ The dissolution rate was reduced to below approximately 1.5%. The resulting modified ion sieve exhibits high lithium adsorption capacity, good hydrophilicity, and excellent ion selectivity, along with low titanium dissolution rate, demonstrating promising prospects for industrial application. Specifically, it includes:
Smart Images

Figure CN122745831A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion sieve adsorption materials technology, specifically relating to a cerium-nitrogen synergistic modified lithium titanate sieve and its preparation method, as well as the application of this material in the selective adsorption, separation and recovery of lithium ions. Background Technology
[0002] With the rapid development of new energy vehicles, energy storage systems, and the electronic information industry, global demand for lithium resources continues to grow. Efficient development of brine lithium resources has become a crucial way to ensure a sustainable supply of lithium. Compared to lithium extraction from ore, brine in salt lakes has advantages such as abundant reserves and low development costs. However, due to the presence of Li... + The concentration was low, but it was accompanied by a large amount of Na. + K + Mg 2+ and Ca 2+ Achieving efficient and selective separation of lithium ions, even among competing ions, remains a significant challenge.
[0003] Lithium-ion sieve adsorption is considered one of the most promising lithium extraction technologies from salt lakes due to its advantages such as high adsorption capacity, good selectivity, recyclability, and environmental friendliness. Among these, titanium-based lithium-ion sieves have attracted widespread attention due to their stable Ti-O framework structure, good acid resistance, low titanium dissolution rate, and high cycle stability. Li₂TiO₃, as a typical precursor for titanium-based lithium-ion sieves, can be converted into H₂TiO₃ lithium-ion sieves after acid leaching for delithiation. H₂TiO₃ exhibits good lithium-ion selectivity and structural stability, and has broad application prospects in the field of lithium extraction from salt lakes.
[0004] However, H₂TiO₃ (HTO) lithium-ion sieves still have certain shortcomings. Due to the limited specific surface area of the material and the insufficient number of surface active sites, the actual lithium adsorption capacity is lower than the theoretical value; at the same time, Li + The slow diffusion rate within the material limits its adsorption kinetics. Furthermore, the structural stability of the material needs further improvement during long-term acid leaching and cyclic adsorption, particularly in complex brine systems, where the adsorption of Li... + The selectivity of lithium-ion sieves is also affected by coexisting ions. Therefore, how to further regulate the crystal structure, electronic structure, and interfacial properties of H2TiO3 lithium-ion sieves to improve their adsorption capacity, ion transport efficiency, and cycle stability has become an important research direction for lithium-ion sieves.
[0005] In recent years, to improve the overall performance of H2TiO3 lithium-ion sieves, researchers have proposed various modification strategies, including morphology control, nanoscale design, defect engineering, heterostructure construction, and element doping. Among these, element doping can effectively control the electronic structure and surface chemical properties of materials while maintaining the stability of the main crystal structure, promoting electron migration and ion diffusion, and improving the adsorption performance of materials. Therefore, it has become an important research direction for optimizing the performance of lithium-ion sieves.
[0006] Introducing metal ions of different valence states into the H₂TiO₃ lattice can effectively control its microstructure, which is one of the most common methods to improve adsorption performance. The hydrothermal synthesis of tungsten (W)-doped H₂TiO₃ lithium ion sieves can increase the interplanar spacing and reduce Ti dissolution; the optimized adsorption capacity reaches 43.01 mg / g, which is 1.4 times that of undoped HTO (Preparation of tungsten-doped Ti-based lithium ion sieves with excellent adsorption performance by hydrothermal method, Journal of Alloys and Compounds, Volume 1005, 15 November 2024, 176058). Cobalt (Co)-doped HTO, prepared by high-temperature calcination, can increase the specific surface area and pore volume, achieving an adsorption capacity of 39.7 mg / g (Preparation and Adsorption Performance Study of Cobalt-doped Lithium Metatitanate Ion Sieves, Applied Chemistry, 2025, Vol. 8). HTO can replace Ti sites by doping with iron (Fe), generating lattice defects and oxygen vacancies, shortening the equilibrium adsorption time by 20 hours, and achieving an adsorption capacity of 37.20 mg / g within 4 hours (Fe-doped H2TiO3 for rapid and efficient lithium extraction from shale gas wastewater, Desalination, Volume 606, 1 July 2025, 118761).
[0007] On the other hand, anion doping is also an important means of improving the electronic structure of materials. N doping can change the local electronic environment around the Ti–O bond, promote electron migration, and induce the formation of oxygen vacancies and defect sites, thus creating a favorable environment for Li. +Adsorption provides more active sites and is beneficial for improving the ion exchange kinetics of materials. Literature reports that nitrogen doping can be achieved through synergistic modification with thiourea (TU) and surfactant (SDS), expanding the lattice and increasing the HTO adsorption capacity (Synergistic regulation of thiourea and SDS on the structure of H2TiO3 and its efficient lithium extraction mechanism, Chemical Engineering Journal, Volume 536, 15 May 2026, 175876). CN118904311A discloses a modification method for titanium-based lithium-ion sieves, preparing modified lithium metatitanate precursors through solid-phase synthesis, sol-gel synthesis, or hydrothermal synthesis; this method enhances the adsorption capacity and adsorption rate of titanium-based lithium-ion sieves through doping with non-metallic ions such as nitrogen, sulfur, or selenium.
[0008] Compared to conventional transition metals, rare earth elements possess a unique 4f electronic structure, variable valence states, and excellent electronic modulation capabilities, demonstrating promising application potential in catalysis, energy storage, and adsorption materials. Among them, Ce exhibits reversible Ce... 3+ / Ce 4+ Redox cycles and excellent oxygen storage and release capabilities can promote electron migration, induce oxygen vacancy formation, and improve interfacial electronic structure, potentially enhancing the adsorption performance and structural stability of lithium-ion sieves. However, research on the application of rare earth elements, especially Ce, in H₂TiO₃ lithium-ion sieves is still relatively limited, and their regulatory mechanisms on the material's interfacial structure and adsorption performance have not yet been fully elucidated.
[0009] Currently, there are few reports on titanium-based lithium-ion sieves that combine CeO2 heterostructure construction with N anion synergistic regulation. Synergistic modification of H2TiO3 lithium-ion sieves through simultaneous Ce and N doping and heterostructure interface construction is expected to provide a new technical solution for the design of high-performance titanium-based lithium-ion sieves and their application in lithium extraction from salt lakes. Summary of the Invention
[0010] The purpose of this invention is to overcome the problems of limited adsorption capacity, slow adsorption kinetics, and insufficient cycle stability of lithium metatitanate ion sieves, and to provide a cerium-nitrogen synergistic modified metatitanate composite lithium ion sieve and its in-situ preparation method. Through synergistic doping modification with Ce and N anions, CeO2 nanoparticles are grown in situ on the surface of a Li2TiO3 precursor, constructing a stable CeO2 / Li2TiO3-N heterostructure. After acid elution and lithium removal, a cerium-nitrogen modified metatitanate composite lithium ion sieve is formed, increasing the number of active sites and Li-2 ions. + Transport efficiency and adsorption performance.
[0011] Another object of the present invention is to provide the application of the aforementioned metatitanic acid composite lithium ion sieve in the selective adsorption of lithium ions.
[0012] In a first aspect, the present invention provides a composite lithium-ion sieve, which adopts the following technical solution:
[0013] A cerium-nitrogen modified metatitanate composite lithium-ion sieve, characterized in that: the composite lithium-ion sieve is a cerium-nitrogen modified lithium titanate composite precursor (CeO2). X / Li2TiO3-N y The delithiation product has x of 0.02~0.1 and y of 0.1~0.2; its active component is H2TiO3, CeO2 nanoparticles are uniformly loaded on the surface of H2TiO3, and N element is doped in the H2TiO3 lattice.
[0014] The composite lithium-ion sieve, designated CeO2 / HTO-N, contains H2TiO3 derived from the lithium-free product of Li2TiO3 after acid leaching in the composite precursor. CeO2 nanoparticles are uniformly dispersed on the surface of the H2TiO3 particles. This composite lithium-ion sieve maintains the layered framework structure of H2TiO3, and its crystal structure remains stable before and after acid leaching. After acid leaching, CeO2 remains stably loaded on the H2TiO3 surface and does not migrate with the lithium. + The nitrogen (N) is removed and detached, forming a tight interfacial contact with H₂TiO₃ to construct a CeO₂ / H₂TiO₃ heterostructure, thus improving the material's structural stability and lithium-ion adsorption performance. N doping alters the local electronic environment around the Ti–O bond, promoting electron migration and further inducing defect site formation, thus enhancing the lithium-ion adsorption capacity of the material. + Adsorption provides more active sites. The composite lithium-ion sieve combines Ce modification with N anion doping, achieving synergistic regulation of interface structure and electronic structure, thereby further improving the adsorption performance, selectivity, and cycle stability of the lithium-ion sieve.
[0015] A second aspect of the present invention provides a method for preparing the above-mentioned CeO2 / HTO-N composite lithium-ion sieve, comprising the following steps:
[0016] (1) Dissolve and mix the titanium source and lithium source in a solvent according to the stoichiometric ratio of Li / Ti in Li2TiO3 (LTO) to obtain a Li2TiO3 precursor mixture;
[0017] (2) Add cerium source and nitrogen source to the above mixture and stir continuously to form a uniform composite precursor slurry;
[0018] (3) After drying the obtained composite precursor slurry, it was calcined in an air atmosphere to obtain the cerium nitrogen modified Li2TiO3 composite precursor, denoted as CeO2 / Li2TiO3–N;
[0019] (4) The composite precursor is placed in an acid solution for acid leaching to remove lithium. After filtration, washing until neutral, and drying, the cerium nitrogen modified composite lithium ion sieve is obtained, denoted as CeO2 / HTO-N.
[0020] The titanium source is selected from any one of titanium dioxide, metatitanic acid, and tetrabutyl titanate. Preferably, it is titanium dioxide or tetrabutyl titanate.
[0021] The lithium source is selected from any one of lithium hydroxide, lithium chloride, lithium carbonate, and lithium acetate. Lithium carbonate or lithium acetate is preferred.
[0022] The cerium source is selected from cerium nitrate, cerium chloride, or cerium oxide. Cerium nitrate is preferred.
[0023] The nitrogen source is selected from urea, melamine, dicyandiamide, thiourea, or ammonia. Urea or melamine is preferred, and urea is even more preferred. When urea or melamine is used as the nitrogen source, it also acts as a structure regulator for the composite precursor, slowly decomposing and releasing nitrogen-containing species during heating to achieve N element doping and promote the uniform dispersion of Ce species on the surface of the composite precursor.
[0024] Preferably, the solution in step (1) is water, C1-C5 low-carbon alcohol, or a mixture of alcohol and water. Ethanol or an aqueous solution of ethanol is preferred.
[0025] Preferably, the molar ratio of titanium to cerium in the composite precursor slurry in step (2) is 1:(0.02~0.10). For example, the Ce / Ti molar ratio is 0.02, 0.04, 0.06, 0.08 or 0.10.
[0026] Preferably, the molar ratio of titanium to nitrogen in the composite precursor slurry in step (2) is 1:(0.1 to 0.2). For example, the N / Ti molar ratio is 0.1, 0.12, 0.15, 0.18 or 0.20.
[0027] Preferably, the calcination temperature in step (3) is 650–850 °C and the calcination time is 2–5 h.
[0028] Preferably, the acid solution used in step (4) for acid leaching and delithiation is one or more of hydrochloric acid, sulfuric acid, nitric acid, and acetic acid.
[0029] Preferably, the concentration of the acid solution in step (4) is 0.10–0.25 mol·L⁻¹. -1 The acid leaching time is 6~48 hours.
[0030] Preferably, the drying temperature in step (4) is 60–80 °C.
[0031] This invention also relates to the application of the composite lithium-ion sieve in the selective adsorption of lithium ions.
[0032] The composite lithium-ion sieve can be used for the selective adsorption and extraction of lithium ions in lithium-ion-containing solutions such as geothermal water, oil and gas field water, salt lake brine and seawater, and has the advantage of high selectivity, especially for salt lake brine with a high magnesium-to-lithium ratio.
[0033] Beneficial effects: The Ce and N synergistic modification of H2TiO3 composite lithium-ion sieve of the present invention modifies the H2TiO3 lithium-ion sieve through Ce and N synergistic doping, simultaneously realizing the formation of CeO2 heterostructure interface and N element doping, synergistically promoting the reconstruction of material electronic structure, oxygen vacancy generation and interface electronic coupling, and improving Li-O3 lithium-ion sieve performance. + This significantly improves the lithium adsorption capacity, selectivity, and cycle stability of lithium-ion sieves by enhancing transport efficiency and ion exchange capacity. 4+ The dissolution rate was reduced to below approximately 1.5%. The resulting modified ion sieve exhibits high lithium adsorption capacity, good hydrophilicity, and excellent ion selectivity, along with low titanium dissolution rate, demonstrating promising prospects for industrial application. Specifically, it includes:
[0034] (1) The high-temperature solid-phase method combined with the in-situ deposition method is used to make Ce species uniformly dispersed on the surface of Li2TiO3 particles, avoiding the problem of agglomeration that is easy to occur in the traditional impregnation method.
[0035] (2) The in-situ formation of CeO2 / Li2TiO3 heterostructure during calcination is beneficial for controlling the electronic structure of the material and increasing the number of active sites and Li + Transmission rate.
[0036] (3) After acid washing and delithiation, a CeO2 / HTO-N composite lithium ion sieve is formed. While maintaining the stability of the main crystal structure, it improves the specific surface area and pore structure of the material, which is conducive to the rapid diffusion of lithium ions.
[0037] (4) The prepared composite lithium-ion sieve has a high lithium-ion adsorption capacity and excellent Li-ion adsorption capacity. + / Mg 2+ With its selectivity, good cycle stability and regeneration performance, it can be applied to the lithium extraction process of liquid lithium resources such as salt lake brine, geothermal water and seawater. Attached Figure Description
[0038] Figure 1 The (CeO2) obtained in Example 1 of this invention 0.06 / Li2TiO3-N 0.1 and (CeO2) 0.06 / H2TiO3-N0.1 XRD patterns;
[0039] Figure 2 The (CeO2) obtained in Example 1 of this invention 0.06 / Li2TiO3-N 0.1 SEM image;
[0040] Figure 3 shows the HTO and (CeO2) prepared in Example 1 of this invention. 0.06 / H2TiO3-N 0.1 Water contact angle diagram;
[0041] Figure 4 The (CeO2) obtained in Example 1 of this invention 0.06 / H2TiO3-N 0.1 Ti 4+ Dissolution rate and Li + Elution rate graph;
[0042] Figure 5 These are the XRD patterns of CeO2 / LTO-N composite lithium-ion sieves obtained with different Ce doping amounts in Examples 1-5 of this invention;
[0043] Figure 6 These are the XRD patterns of CeO2 / LTO-N composite lithium-ion sieves obtained with different Ce doping amounts in Examples 6-10 of this invention;
[0044] Figure 7 These are the XRD patterns of CeO2 / LTO-N composite materials obtained with different Ce doping amounts in Examples 11-15 of this invention. Detailed Implementation
[0045] The following examples are only used to illustrate the best implementation of the present invention, and the scope of protection of the present invention is not limited to the specific implementation.
[0046] Example 1
[0047] (1) (CeO2) 0.06 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0048] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.01 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio of HTO, and the mixture was magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.2605 g, 0.0006 mol) and melamine (0.1051 g, 0.008 mol) were added, and the mixture was stirred continuously until fully mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.06 / Li2TiO3-N 0.1 Composite precursor. The obtained composite precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.06 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0049] Quantitative (CeO2) 0.06 / Li2TiO3-N 0.1 At 0.1 mol·L –1 Lithium was removed by acid leaching in HCl solution for 24 hours, and the Li content during the acid leaching process was measured. + Elution rate and Ti 4+ The solution loss rate is calculated using the following formula (1):
[0050] (1)
[0051] Wherein, R is the ratio of the mass of element M in the solution to the mass of element M in the precursor;
[0052] M is the element to be tested, Li. + or Ti 4+ ;
[0053] The mass concentration of element M in solution C(M), mg·L⁻¹ -1 ;
[0054] V is the volume of the solution, in L;
[0055] m(M) is the mass of element M in the precursor of acid leaching and delithiation, in g.
[0056] (2) Adsorption test
[0057] 1 g of (CeO2) was added at 25℃. 0.06 / H2TiO3-N 0.1Add to 1 L of LiOH solution (100 mg•L⁻¹) and determine its adsorption capacity. and adsorption equilibrium time T .
[0058] At 25 °C, 1 g of (CeO2) was added. 0.06 / H2TiO3-N 0.1 A static adsorption experiment was conducted by adding a composite lithium-ion sieve to 1 L of simulated salt lake brine, and the pH of the solution was adjusted to 8. The simulated brine contained Li. + Na + K + Ca 2+ and Mg 2+ The coexisting ions have the following initial concentrations: C Li+ = 73.23 mg·L -1 C Na+ = 232.8 mg·L -1 C Ca2+ = 169.5 mg·L -1 C K+ = 299.3 mg·L -1 and C Mg2+ = 337.6 mg·L -1 After adsorption, the changes in the concentration of each ion in the solution were measured, and the effect of the material on Li was calculated. + adsorption capacity and Li + / Mg 2+ Selectivity for the separation of coexisting ions.
[0059] See Application Example 1 for the results.
[0060] Figure 1 The composite precursor (CeO2) obtained in Example 1 0.06 / Li2TiO3-N 0.1 and composite ion sieve sample (CeO2) 0.06 / H2TiO3-N 0.1 The XRD pattern was obtained. Based on the XRD pattern, its crystallinity was calculated to be 78%.
[0061] Figure 2 It shows (CeO2). 0.06 / Li2TiO3-N 0.1 The SEM image shows that the sample is composed of nanoparticles that form a uniform aggregate structure with close contact between particles of different sizes. The CeO2 phase is loaded on the LTO-N surface, forming a continuous interfacial contact structure, indicating that a CeO2 / LTO-N heterostructure was successfully constructed in the composite material.
[0062] Figure 3aThe water contact angle diagram of H2TiO3 is shown. Figure 3b It shows (CeO2). 0.06 / H2TiO3-N 0.1 Water contact angle diagram, (CeO2) 0.06 / H2TiO3-N 0.1 The composite material has a smaller water contact angle, indicating that its surface hydrophilicity is better than that of HTO, which can improve the wettability of the material in aqueous solution.
[0063] Figure 4 It shows (CeO2). 0.06 / Li2TiO3-N 0.1 Ti 4+ Dissolution rate and Li + The elution rate graph shows (CeO2). 0.06 / Li2TiO3-N 0.1 After 12 h of pickling treatment, its Li + The elution rate reached 98%, Ti 4+ The dissolution loss rate remained below 1.5%, indicating that (CeO2) 0.06 / Li2TiO3-N 0.1 It has good structural stability and excellent adsorption performance.
[0064] Example 2
[0065] (1) (CeO2) 0.02 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0066] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.0868 g, 0.0002 mol) and melamine (0.1051 g, 0.008 mol) were added and stirred continuously until fully mixed to form a homogeneous precursor solution. The resulting mixture was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.02 / Li2TiO3-N 0.1 Composite precursor. The obtained composite precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.02 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0067] (2) Adsorption test
[0068] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0069] The sample (CeO2) obtained in Example 2 0.02 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 5 Based on the XRD pattern, its crystallinity was calculated to be 76%.
[0070] Example 3
[0071] (1) (CeO2) 0.04 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0072] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.1736 g, 0.0004 mol) and melamine (0.1051 g, 0.008 mol) were added and continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting mixture was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.04 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.04 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0073] (2) Adsorption test
[0074] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0075] The sample (CeO2) obtained in Example 3 0.04 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 5 Based on the XRD pattern, its crystallinity was calculated to be 73%.
[0076] Example 4
[0077] (1) (CeO2) 0.08 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0078] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.3473 g, 0.0008 mol) and melamine (0.1051 g, 0.008 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.08 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.08 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0079] (2) Adsorption test
[0080] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0081] The sample (CeO2) obtained in Example 4 0.08 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 5 Based on the XRD pattern, its crystallinity was calculated to be 88%.
[0082] Example 5
[0083] (1) (CeO2) 0.1 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0084] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.4342 g, 0.001 mol) and melamine (0.1051 g, 0.008 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.1 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.1 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0085] (2) Adsorption test
[0086] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0087] The sample (CeO2) obtained in Example 5 0.1 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 5 Based on the XRD pattern, its crystallinity was calculated to be 89%.
[0088] Example 6
[0089] (1) (CeO2) 0.02 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0090] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.0868 g, 0.0002 mol) and urea (0.06 g, 0.001 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.02 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.02 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0091] (2) Adsorption test
[0092] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0093] The sample (CeO2) obtained in Example 6 0.02 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 6 Based on the XRD pattern, its crystallinity was calculated to be 82%.
[0094] Example 7
[0095] (1) (CeO2) 0.04 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0096] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.1736 g, 0.0004 mol) and urea (0.06 g, 0.001 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.04 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.04 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0097] (2) Adsorption test
[0098] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0099] The sample (CeO2) obtained in Example 7 0.04 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 6 Based on the XRD pattern, its crystallinity was calculated to be 79%.
[0100] Example 8
[0101] (1) (CeO2) 0.06 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0102] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.2605 g, 0.0006 mol) and urea (0.06 g, 0.001 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.06 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.06 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0103] (2) Adsorption test
[0104] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0105] The sample (CeO2) obtained in Example 8 0.06 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 6 Based on the XRD pattern, its crystallinity was calculated to be 83%.
[0106] Example 9
[0107] (1) (CeO2) 0.08 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0108] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.3473 g, 0.0008 mol) and urea (0.06 g, 0.001 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.08 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.08 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0109] (2) Adsorption test
[0110] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0111] The sample (CeO2) obtained in Example 9 0.08 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 6 Based on the XRD pattern, its crystallinity was calculated to be 86%.
[0112] Example 10
[0113] (1) (CeO2) 0.1 / H2TiO3-N 0.1 Preparation of composite lithium-ion sieves
[0114] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.4342 g, 0.001 mol) and urea (0.06 g, 0.001 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.1 / Li2TiO3-N 0.1 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.1 / H2TiO3-N 0.1 Composite lithium-ion sieve.
[0115] (2) Adsorption test
[0116] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0117] The sample (CeO2) obtained in Example 10 0.1 / Li2TiO3-N 0.1 The XRD pattern can be found Figure 6 Based on the XRD pattern, its crystallinity was calculated to be 81%.
[0118] Comparative Example 11
[0119] (1) (CeO2) 0.02 Preparation of H2TiO3 composite materials
[0120] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio, and the mixture was magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.0868 g, 0.0002 mol) was added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.02 / Li2TiO3 composite material. The obtained precursor was placed in 0.1 mol / L HCl solution for 8 h for acid leaching to complete the Li2TiO3 composite material. + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.02 / H2TiO3 composite lithium ion sieve.
[0121] (2) Adsorption test
[0122] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0123] The sample (CeO2) obtained in Example 11 0.02 The XRD pattern of Li2TiO3 can be found here. Figure 7 Based on the XRD pattern, its crystallinity was calculated to be 74%.
[0124] Comparative Example 12
[0125] (1) (CeO2) 0.04 Preparation of H2TiO3 composite materials
[0126] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio, and the mixture was magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.1736 g, 0.0004 mol) was added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then placed in a muffle furnace and calcined at 750 °C for 3 h to obtain (CeO2). 0.04 / Li2TiO3 composite material. The obtained precursor was placed in 0.1 mol / L HCl solution for 8 h for acid leaching to complete the Li2TiO3 composite material. + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to finally obtain (CeO2). 0.04 / H2TiO3 composite lithium ion sieve.
[0127] (2) Adsorption test
[0128] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0129] The sample (CeO2) obtained in Example 12 0.04 The XRD pattern of Li2TiO3 can be found here. Figure 7 Based on the XRD pattern, its crystallinity was calculated to be 73%.
[0130] Comparative Example 13
[0131] (1) (CeO2) 0.06 Preparation of H2TiO3 composite materials
[0132] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio, and the mixture was magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.2605 g, 0.0006 mol) was added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.06 / Li2TiO3 composite material. The obtained precursor was placed in 0.1 mol / L HCl solution for 8 h for acid leaching to complete the Li2TiO3 composite material. + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to finally obtain (CeO2). 0.06 / H2TiO3 composite lithium ion sieve.
[0133] (2) Adsorption test
[0134] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0135] The sample (CeO2) obtained in Example 13 0.06 The XRD pattern of Li2TiO3 can be found here. Figure 7 Based on the XRD pattern, its crystallinity was calculated to be 75%.
[0136] Comparative Example 14
[0137] (1) (CeO2) 0.08 Preparation of H2TiO3 composite materials
[0138] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio, and the mixture was magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.3473 g, 0.0008 mol) was added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then placed in a muffle furnace and calcined at 750 °C for 3 h to obtain (CeO2). 0.08 / Li2TiO3 composite material. The obtained precursor was placed in 0.1 mol / L HCl solution for 8 h for acid leaching to complete the Li2TiO3 composite material. + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to finally obtain (CeO2). 0.08 / H2TiO3 composite lithium ion sieve.
[0139] (2) Adsorption test
[0140] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0141] The sample (CeO2) obtained in Example 14 0.08 The XRD pattern of Li2TiO3 can be found here. Figure 7 Based on the XRD pattern, its crystallinity was calculated to be 81%.
[0142] Comparative Example 15
[0143] (1) (CeO2) 0.1 Preparation of H2TiO3 composite materials
[0144] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio, and the mixture was magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.4342 g, 0.001 mol) was added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then placed in a muffle furnace and calcined at 750 °C for 3 h to obtain (CeO2). 0.1 / Li2TiO3 composite material. The obtained precursor was placed in 0.1 mol / L HCl solution for 8 h for acid leaching to complete the Li2TiO3 composite material. + / H +Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.1 / H2TiO3 composite lithium ion sieve.
[0145] (2) Adsorption test
[0146] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0147] The sample (CeO2) obtained in Example 15 0.1 The XRD pattern of Li2TiO3 can be found here. Figure 7 Based on the XRD pattern, its crystallinity was calculated to be 77%.
[0148] Example 16
[0149] (1) (CeO2) 0.06 / H2TiO3-N 0.15 Preparation of composite lithium-ion sieves
[0150] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.2605 g, 0.0006 mol) and urea (0.09 g, 0.0015 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.06 / Li2TiO3-N 0.15 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.06 / H2TiO3-N 0.15 Composite lithium-ion sieve.
[0151] (2) Adsorption test
[0152] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0153] Example 17
[0154] (1) (CeO2) 0.06 / H2TiO3-N 0.2 Preparation of composite lithium-ion sieves
[0155] Lithium carbonate (0.775 g, 0.0105 mol) and titanium dioxide (0.798 g, 0.010 mol) were added to anhydrous ethanol according to the Li / Ti stoichiometric ratio and magnetically stirred until fully mixed. Then, cerium nitrate hexahydrate (0.2605 g, 0.0006 mol) and urea (0.12 g, 0.002 mol) were added, and the mixture was continuously stirred until fully dispersed and mixed to form a homogeneous precursor solution. The resulting solution was dried in an oven at 80 °C for 24 h to obtain a dry gel precursor. The sample was then calcined in a muffle furnace at 750 °C for 3 h to obtain (CeO2). 0.06 / Li2TiO3-N 0.2 Composite precursor. The obtained precursor was immersed in 0.1 mol / L HCl solution for 8 h to complete the Li... + / H + Ion exchange. After acid leaching, the solution was filtered, washed with deionized water until the filtrate was nearly neutral, and then dried at 60 °C for 12 h to obtain (CeO2). 0.06 / H2TiO3-N 0.2 Composite lithium-ion sieve.
[0156] (2) Adsorption test
[0157] The adsorption test was performed using the same method as in Example 1, and the results are shown in Application Example 1.
[0158] Application Example 1
[0159] (1) Adsorption capacity and adsorption equilibrium time T test:
[0160] Take 1 g of each of the CeO2 / HTO-N lithium ion sieves prepared in Examples 1-15 and add them to 1 L of LiOH solution (100 mg·L⁻¹). -1 The solution was stirred and adsorption tests were conducted. The concentration of Li in the solution was measured using ICP (inductively coupled plasma). + initial concentration ( ) and instantaneous concentration ( (This continues until adsorption equilibrium is reached.) Until it remains essentially unchanged. The adsorption capacity of CeO2 / HTO-N It is calculated using formula (2).
[0161] (2)
[0162] in: Take the concentration value at adsorption equilibrium, mg·L -1 ;
[0163] V represents the solution volume, in L;
[0164] m represents the mass of the lithium-ion sieve, in grams.
[0165] (2) Adsorption cycle test (calculated based on an 80% decrease in adsorption capacity):
[0166] 1 g CeO2 / HTO-N in LiOH solution (100 mg·L⁻¹) -1 The cycling performance of CeO2 / HTO-N after adsorption was assessed using a 0.1 mol·L⁻¹ solution. -1 After HCl washing, the adsorption experiment was repeated, and the adsorption capacity was measured after each cycle until the adsorption capacity decreased to 80% of the initial value, and the number of cycles was obtained. The test method, conditions and calculation formula are the same as formula (2).
[0167] (3) Adsorption selectivity test:
[0168] 1 g of CeO2 / HTO-N was placed at 25 °C in a solution containing Li at pH = 8. + Na + Ca 2+ K + and Mg 2+ The initial concentrations of ions in the salt lake brine are as follows: C Li+ = 73.23 mg·L -1 C Na+ = 232.8 mg·L -1 C Ca2+ = 169.5 mg·L -1 C K+ = 299.3 mg·L -1 and C Mg2+ = 337.6 mg·L -1 Adsorption was performed for 24 h, and the adsorption selectivity was determined. The concentration of Li in the solution was measured using ICP. + and the initial concentration of hetero ions ( ) and instantaneous concentration ( Allocation coefficient () and separation factor The results are obtained by formulas (3) and (4) respectively.
[0169] (3)
[0170] (4)
[0171] in: The partition coefficient is expressed in mL·g. -1 ;
[0172] V is the solution volume, in L;
[0173] m is the mass of the lithium-ion sieve sample, in grams;
[0174] C e The concentration of remaining ions in the solution is expressed in mg / g. -1 .
[0175] The results are shown in Table 1 (using Li as an example). + For Mg 2+ (For example, the separation factor).
[0176] Table 1 Adsorption performance test results
[0177]
Claims
1. A cerium-nitrogen modified metatitanic acid composite lithium-ion sieve, characterized in that: The composite lithium-ion sieve system uses cerium nitrogen-modified lithium titanate composite precursor (CeO2). X / Li2TiO3-N y The delithiation product has x of 0.02~0.1 and y of 0.1~0.2; its active component is H2TiO3, CeO2 nanoparticles are uniformly loaded on the surface of H2TiO3, and N element is doped in the H2TiO3 lattice.
2. A method for preparing a cerium-nitrogen modified metatitanic acid composite lithium-ion sieve, characterized in that, Includes the following steps: (1) Dissolve the titanium source and lithium source in a solvent according to the stoichiometric ratio of Li / Ti in Li2TiO3 and mix them evenly to prepare a Li2TiO3 precursor mixture; (2) Add cerium source and nitrogen source to the above mixture and stir continuously to form a uniform composite precursor slurry; (3) After drying the obtained composite precursor slurry, it was calcined in an air atmosphere to obtain the cerium nitrogen modified Li2TiO3 composite precursor, denoted as CeO2 / Li2TiO3–N; (4) The composite precursor is placed in an acid solution for acid leaching to remove lithium. After filtration, washing until neutral, and drying, the cerium nitrogen modified composite lithium ion sieve is obtained, denoted as CeO2 / HTO-N.
3. The preparation method according to claim 2, characterized in that, The titanium source is selected from any one of titanium dioxide, metatitanic acid, and tetrabutyl titanate.
4. The preparation method according to claim 2, characterized in that, The lithium source is selected from any one of lithium hydroxide, lithium chloride, lithium carbonate, and lithium acetate.
5. The preparation method according to claim 2, characterized in that, The cerium source is selected from cerium nitrate, cerium chloride, or cerium oxide.
6. The preparation method according to claim 2, characterized in that, The nitrogen source is selected from urea, melamine, dicyandiamide, thiourea, or ammonia.
7. The preparation method according to claim 2, characterized in that, The solution mentioned in step (1) is water, C1-C5 low carbon alcohol, or a mixture of alcohol and water.
8. The preparation method according to claim 2, characterized in that, The molar ratio of titanium to cerium in the composite precursor slurry described in step (2) is 1:(0.02~0.10).
9. The preparation method according to claim 2, characterized in that, The molar ratio of titanium to nitrogen in the composite precursor slurry described in step (2) is 1:(0.1~0.2).
10. The application of the cerium nitrogen-modified metatitanic acid composite lithium ion sieve according to claim 1 in the selective adsorption of lithium ions.
Citation Information
Patent Citations
Modification method of titanium lithium ion sieve
CN118904311A